PENGARUH LKS BERORIENTASI PENDEKATAN SAINTIFIK DALAM METODE QUANTUM LEARNING TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMA NEGERI 2 PADANG - Desestra Desestra; Hufri Hufri; Fatni MUfit (PILLAR OF PHYSICS EDUCATION, 2015)
The background of this research is still at least a scientific approach oriented teaching materials including student worksheet (LKS) and learning methods that are less attractive, including of SMA state 2 Padang. In curriculum requires tecahers to be able to utilize the entire potensial of the students in the teaching, so that the student centered learning. One approach with regard to these demands is the scientific approach, so that learning can be implemented with either the necessary teaching materials and methods that support the learning process. This purpose of research to investigate the influence of LKS oriented scientific approach in the method of quantum learning to learning outcomes-physics class X students of SMA state 2 Padang in the school year 2014/2015. This type of research is a "quasi experimenal" with the draft "only randomized control group design. Sampling was done by using cluster random sampling. Data research include learning outcomes in the cognitive, affective, and psychomotor. The research instrument in the form of a written test for cognitive learning outcomes, observation sheet for affective learning outcomes, and the scoring rubric for the assessment of psychomotor performance. Data analysis of learning outcomes in the cognitive and psychomotor the experimental class is better than the control class, except for affective learning outcome. On the affective obtained th = 0.955 < tt = 1.67 , on the cognitive obtained th = 2.31 > tt = 1.67, and the psychomotor obtained th = 2.50 > tt = 1.67. Based on the data analysis can be presented  result of research. The hypothesis that there is a significant effect of giving LKS oriented scientific approach in the method of quantum learning to learning outcomes-Physics class X students of SMA state 2 Padang can be accepted for learning outcomes in the cognitive and psychomotor except for affective learning outcome at the 0.05 significance level